Outcome of Children With Hypodiploid Acute Lymphoblastic Leukemia: A Retrospective Multinational Study - Pui, Ching-Hon (J Clin Oncol, 2019)
PURPOSE: We determined the prognostic factors and utility of allogeneic hematopoietic cell transplantation among children with newly diagnosed hypodiploid acute lymphoblastic leukemia (ALL) treated in contemporary clinical trials. PATIENTS AND METHODS: This retrospective study collected data on 306 patients with hypodiploid ALL who were enrolled in the protocols of 16 cooperative study groups or institutions between 1997 and 2013. The clinical and biologic characteristics, early therapeutic responses as determined by minimal residual disease (MRD) assessment, treatment with or without MRD-stratified protocols, and allogeneic transplantation were analyzed for their impact on outcome. RESULTS: With a median follow-up of 6.6 years, the 5-year event-free survival rate was 55.1% (95% CI, 49.3% to 61.5%), and the 5-year overall survival rate was 61.2% (95% CI, 55.5% to 67.4%) for the 272 evaluable patients. Negative MRD at the end of remission induction, high hypodiploidy with 44 chromosomes, and treatment in MRD-stratified protocols were associated with a favorable prognosis, with a 5-year event-free survival rate of 75% (95% CI, 66.0% to 85.0%), 74% (95% CI, 61.0% to 89.0%), and 62% (95% CI, 55.0% to 69.0%), respectively. After exclusion of patients with high hypodiploidy with 44 chromosomes and adjustment for waiting time to transplantation and for covariables in a Poisson model, disease-free survival did not differ significantly (P = .16) between the 42 patients who underwent transplantation and the 186 patients who received chemotherapy only, with an estimated 5-year survival rate of 59% (95% CI, 46.5% to 75.0%) versus 51.5% (95% CI, 44.7% to 59.4%), respectively. Transplantation produced no significant impact on outcome compared with chemotherapy alone, especially among the subgroup of patients who achieved a negative MRD status upon completion of remission induction. CONCLUSION: MRD-stratified treatments improved the outcome for children with hypodiploid ALL. Allogeneic transplantation did not significantly improve outcome overall and, in particular, for patients who achieved MRD-negative status after induction.